An electrochemical DNA biosensor fabricated from graphene decorated with graphitic nanospheres - Raja Zaidatul Akhmar, Raja Jamaluddin; Tan, Ling Ling; Chong, Kwok Feng; Heng, Lee Yook (IOP Publishing Ltd, 2020)
Graphene decorated with graphitic nanospheres functionalized with pyrene butyric acid (PBA) is used for the first time to fabricate a DNA biosensor. The electrode was formed by attaching a DNA probe onto PBA, which had been stacked onto a graphene material decorated with graphene nanospheres (GNSs). The nanomaterial was drop-coated onto a carbon screen-printed electrode (SPE) to create the GNS-PBA modified electrode (GNS-PBA/SPE). A simple method was used to produce GNS by annealing graphene oxide (GO) solution at high temperature. Field emission scanning electron micrographs confirmed the presence of a spherical shape of GNS with a diameter range of 40–80 nm. A stable and uniform PBA-modified GNS (GNS-PBA) was obtained with a facile ultrasonication step. Thus allowing aminated DNA probes of genetically modified (GM) soybean to be attached to the nanomaterials to form the DNA biosensor. The GNS-PBA/SPE exhibited excellent electrical conductivity via cyclic voltammetry (CV) and differential pulse voltammetry (DPV) tests using potassium ferricyanide (K3[Fe(CN)6]) as the electroactive probe. By employing an anthraquinone monosulfonic acid (AQMS) redox intercalator as the DNA hybridization indicator, the biosensor response was evaluated using the DPV electrochemical method. A good linear relationship between AQMS oxidation peak current and target DNA concentrations from 1.0 × 10−16 to 1.0 × 10−8 M with a limit of detection (LOD) of less than 1.0 × 10−16 M was obtained. Selectivity experiments revealed that the voltammetric GM DNA biosensor could discriminate complementary sequences of GM soybean from non-complementary sequences and hence good recoveries were obtained for real GM soybean sample analysis. The main advantage of using GNS is an improvement of the DNA biosensor analytical performance.